Studi Komparatif Hukum Taurat dan Peraturan Menteri Ketenagakerjaan No. 2 Tahun 2015 tentang Perlindungan Pekerja Rumah Tangga - Bunga, Ferdi Toding; Handayani, Dwi Maria (Societas Dei: Jurnal Agama dan Masyarakat, 2025)
Domestic workers are one of the most vulnerable groups to exploitation and structural violence in modern society. Although Minister of Manpower Regulation No. 2 of 2015 has established basic protections for domestic workers, this legal protection does not yet have adequate legal force. This situation is worsened by the fact that the Draft Law on the Protection of Domestic Workers has not yet been passed, despite being delayed since 2004 (more than 20 years). On the other hand, the Torah in the Bible contains provisions regarding slaves. Although rooted in an ancient social system, it embodies principles of justice and compassion that were radical for its time. Therefore, this article presents a comparison between the provisions regarding slaves in the Torah Law and modern regulations regarding domestic workers through a theological ethical approach. The main objective of this study is to demonstrate that principles, such as liberation, respect for human dignity, and protection of vulnerable groups, contained in the Torah Law, can serve as a reflective foundation for the struggle for social justice for domestic workers in Indonesia. In addition, this study emphasizes the significance of structural and spiritual reform of the domestic work system through a transformative faith approach.